Prevention of coronary heart disease : c - World Health Organization; Report of a WHO Expert Committee (Geneva : World Health Organization, 1982)
The landmark report that established the scientific basis and rationale for public health policy and community action programmes to prevent coronary heart disease. Specific recommendations are based on the need to modify characteristics of life-style and the environment that form the underlying causes of coronary heart disease. Among its proposals, the report puts forward a three-pronged prevention plan involving a population strategy aimed at tackling the underlying causes of mass coronary heart disease, a high-risk strategy aimed at bringing preventive care to those at special risk, and secondary prevention programmes involving strategies to arrest the disease and prevent recurrences among those already afflicted. Since its publication, the report has had a major impact on prevention planning and action in a number of countries.
Keywords: Prevention of Coronary heart disease